The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.neuropharm.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The roles of nerve growth factor and cholecystokinin in the enhancement of morphine analgesia in a rodent model of central nervous system inflammation

Abstract: Animal models of inflammatory pain are characterized by the release of inflammatory mediators such as cytokines and neurotrophic factors, and enhanced analgesic sensitivity to opioids. In this study, we examine the mechanisms underlying this effect, in particular the roles of cholecystokinin (CCK) and nerve growth factor (NGF), in an animal model of central nervous system (CNS) inflammation induced by spinal administration of lipopolysaccharide (LPS). Although spinal administration of LY-225910 (25 ng), a CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…When the tissues were under noxious stimuli, NGF could bind with the receptors, activated neuronal terminal TrkA and P75 receptors, 21,22 and regulated the internal flow of calcium ions, thereby activating the intracellular signaling cascade reaction, modulating and activating different ion channels, causing central sensitization, and resulting in pain-related hypersensitivity or allodynia. 23,24 In this study, the doses of intrathecally injected anti-NGF and NGF were 10 mg, which is consistent with that of Obata et al 25 and Xanthos et al 26 in studying inflammatory pain and neuropathic pain. The pain-related behavioral tests showed that after intrathecally injected anti-NGF, the number of spontaneous foot constriction was decreased, the heat radiation latency was prolonged, and PWMT was increased, suggesting that anti-NGF could significantly alleviate the effects of CIBP in rats; while the intrathecal injection of anti-NGF into the sham group showed no pain-related behavioral changes, suggesting that NGF did not participate the pain signal transduction in normal rats or could not play a major role, meanwhile, it is also suggested that NGF played an important role in the occurrence and development of CIBP.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When the tissues were under noxious stimuli, NGF could bind with the receptors, activated neuronal terminal TrkA and P75 receptors, 21,22 and regulated the internal flow of calcium ions, thereby activating the intracellular signaling cascade reaction, modulating and activating different ion channels, causing central sensitization, and resulting in pain-related hypersensitivity or allodynia. 23,24 In this study, the doses of intrathecally injected anti-NGF and NGF were 10 mg, which is consistent with that of Obata et al 25 and Xanthos et al 26 in studying inflammatory pain and neuropathic pain. The pain-related behavioral tests showed that after intrathecally injected anti-NGF, the number of spontaneous foot constriction was decreased, the heat radiation latency was prolonged, and PWMT was increased, suggesting that anti-NGF could significantly alleviate the effects of CIBP in rats; while the intrathecal injection of anti-NGF into the sham group showed no pain-related behavioral changes, suggesting that NGF did not participate the pain signal transduction in normal rats or could not play a major role, meanwhile, it is also suggested that NGF played an important role in the occurrence and development of CIBP.…”
Section: Discussionsupporting
confidence: 89%
“…25 and Xanthos et al. 26 in studying inflammatory pain and neuropathic pain. The pain-related behavioral tests showed that after intrathecally injected anti-NGF, the number of spontaneous foot constriction was decreased, the heat radiation latency was prolonged, and PWMT was increased, suggesting that anti-NGF could significantly alleviate the effects of CIBP in rats; while the intrathecal injection of anti-NGF into the sham group showed no pain-related behavioral changes, suggesting that NGF did not participate the pain signal transduction in normal rats or could not play a major role, meanwhile, it is also suggested that NGF played an important role in the occurrence and development of CIBP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that many animal models of inflammatory pain are characterized by the release of neurotrophic factors, 28 , 38 , 40 , 42 and that nerve growth factor may function as a key molecular switch that alters dopamine receptor, DOPr, function under sustained opioid stimulation. 42 , 45 Therefore, we also think that the mechanisms in both our models are all involved in the changes among the neurotrophic factors.…”
Section: Discussionmentioning
confidence: 99%